Utilization of Oil Palm Shell Waste (Elaeis guineensis Jacq) into Activated Charcoal - Ayuningtias, Fanny Sania; Barus, Linda; Indarwati, Suami (Poltekkes Kemenkes Tanjung Karang, 2025)
Oil palm shells are solid waste generated from the palm oil industry. The processing of oil palm shells into activated charcoal has not yet been optimized, despite the high demand for activated charcoal in various industries, such as desulfurization in gas purification and LNG processing, as well as filtration processes. Therefore, the quality of activated charcoal depends on the carbonization and activation process. This study aims to determine whether oil palm shells can be converted into activated charcoal using H₃PO₄ as an activating agent at concentrations of 8%, 9%, and 10%, and soaking times of 20, 22, and 24 hours, by the Indonesian National Standard (SNI) for activated charcoal. This study employs a pre-experimental, one-shot case study design. The treatment applied includes the independent variables of H₃PO₄ concentrations (8%, 9%, 10%) and soaking durations (20, 22, 24 hours). The carbonization temperature for all samples was 450–500°C for 0.5 hours. The dependent variable is the resulting activated charcoal powder that meets SNI standards. Activated charcoal with an 8% H₃PO₄ concentration and a 20-hour soaking time yielded the following results: a moisture content of 10.64%, an ash content of 2.66%, and a calorific value of 3,678.43 cal/g. With 9% H₃PO₄ and 20-hour soaking: 9.88% moisture, 2.95% ash, and 4,955.1 cal/g. With 10% H₃PO₄ and 20-hour soaking: 8.21% moisture, 3.53% ash, and 6,190.58 cal/g. The best result, according to SNI 1683-2021